Combined Clagett procedure, negative pressure therapy, and thoracomyoplasty for treatment of late-onset postpneumonectomy empyema necessitatis - Schreiner, Waldemar; Dudek, Wojciech; Sirbu, Horia (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Late-onset post-pneumonectomy empyema necessitatis can occur many years after the surgery and is a life-threatening condition. A 58-year-old male presented with empyema necessitatis 18 years after undergoing pneumonectomy. He was successfully treated with a modified two-stage Clagett procedure and ambulatory negative pressure as the bridge between the stages. The 72-month follow-up was uneventful. The complete obliteration of the rigid and wide residual postpneumonectomy cavity was necessary to avoid re-recurrence of the infection.